Enrolment time as a requirement for face recognition biometric systems - Sá, Vítor (2021)
The performance of a biometric system depends on the accuracy, the processing speed, the template size, and the time necessary for enrolment. This last factor is not much addressed in literature. In this work we collected information about the users' availability for enrolment in respect to face recognition biometrics. Were involved in testing 26 randomly chosen people. The results are presented globally, by sex, by age group and by previous experience in the use of the technology. We found that there is a generalized positive predisposition for enrolment that is expressed in some by the predisposition to try for many times and in others to try over a long time, and that it may be the youngest and the oldest the least available.